2021
DOI: 10.1007/s10055-021-00586-3
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of immersive virtual reality adoption intention: a multi-group analysis in chemical industry settings

Abstract: The present study uses the modified Unified Theory of Acceptance and Use of Technology 2 to examine the effect of factors such as performance expectancy (PE), effort expectancy (EE), social influence (SI), and hedonic motivation (HM) that may motivate operators and employees to adopt IVR-based technology into their training. Results of a multi-group analysis based on nationality, prior IVR experience, and/or length of work experience, to analyse the potential similarities and/or differences in perception and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…As examples of technology-centric VR studies, Ropelato et al (2021) and Thomas and Rosenberg (2019) presented and examined algorithms for "hyper-reoriented walking" and "redirected walking" in VR, that is, steering algorithms that continuously redirect the user in order to make the virtual environment larger than the available physical space. As an example of a more user-centric VR study, Toyoda et al (2021), among others, investigated the drivers of immersive virtual reality adoption intention. Most of the technologycentric VR studies have focused on VR systems in general with gaming as just one of the application areas, whereas numerous user-centric VR studies have focused on VR gaming particularly.…”
Section: Virtual Reality Gaming and Related Acceptance Researchmentioning
confidence: 99%
“…As examples of technology-centric VR studies, Ropelato et al (2021) and Thomas and Rosenberg (2019) presented and examined algorithms for "hyper-reoriented walking" and "redirected walking" in VR, that is, steering algorithms that continuously redirect the user in order to make the virtual environment larger than the available physical space. As an example of a more user-centric VR study, Toyoda et al (2021), among others, investigated the drivers of immersive virtual reality adoption intention. Most of the technologycentric VR studies have focused on VR systems in general with gaming as just one of the application areas, whereas numerous user-centric VR studies have focused on VR gaming particularly.…”
Section: Virtual Reality Gaming and Related Acceptance Researchmentioning
confidence: 99%
“…Further, Henseler's MGA (PLS-MGA) [66] was applied to analyze group-specific differences [68,71] . Henseler's MGA is a nonparametric test that generates boostrapping results for each group [66,68,69] .…”
Section: Multi-group Analysismentioning
confidence: 99%
“…Another potential roadblock is elderly workers’ reluctance to adopt modern technology. Analysis of a survey revealed that expert operators were slightly hesitant to adopt VR for training purposes . Nonetheless, problems related to simulator sickness and willingness to adapt to the technology can be overcome by giving users enough time to acquaint themselves with the usage of VR technology.…”
Section: Virtual Realitymentioning
confidence: 99%